Work per stroke - Kleshnev, V. (Rowing Biomechanics Newsletter, 2014)
This very important biomechanical variable is not used by coaches and rowers very often yet. We are now focusing on the work per stroke (WpS) and defining its main relationships with the rower`s performance.